2009
DOI: 10.1089/pho.2008.2300
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Quality of Life of An Oncological Patient by Laser Phototherapy

Abstract: Normal oral function and consequent improvements in the quality of life of this oncologic patient were observed with LPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
32

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 19 publications
2
47
1
32
Order By: Relevance
“…The use of therapeutic laser in the present study showed positive outcomes and the efficacy of laser to prevent and treat OM in patients subjected to HSCT, chemotherapy and radiotherapy, in accordance with data found in the literature (8,(11)(12)(13)(14)(15)(16)18,20) and the results were similar to those obtained by Antunes et al (12). The outcomes of the present study add to the evidence that therapeutic laser can be an effective option for the prevention and treatment of OM in patients subjected to HSCT with the absence of adverse effects or discomfort, as suggested by other authors (11,13).…”
Section: Discussionsupporting
confidence: 92%
“…The use of therapeutic laser in the present study showed positive outcomes and the efficacy of laser to prevent and treat OM in patients subjected to HSCT, chemotherapy and radiotherapy, in accordance with data found in the literature (8,(11)(12)(13)(14)(15)(16)18,20) and the results were similar to those obtained by Antunes et al (12). The outcomes of the present study add to the evidence that therapeutic laser can be an effective option for the prevention and treatment of OM in patients subjected to HSCT with the absence of adverse effects or discomfort, as suggested by other authors (11,13).…”
Section: Discussionsupporting
confidence: 92%
“…LPT is based on nonthermal effects of light on biological tissues, and its use in the prevention and treatment of mucositis induced by antineoplastic treatment has presented promising results, especially in clinical studies (1,3,4,13). The effect of LPT is based on its ability to modulate several metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Zanin et al (1) and Lopes et al (17) reported that in their studies all patients under RT who received LPT completed the planned RT treatment, whereas patients not treated with LPT had to interrupt the RT because of decreased immunity caused by secondary asthenia and deglutition difficulties, which impacted their survival. Several protocols have been used for treating oral mucositis and the observed results sometimes differ (1,3,4,13,16,17). It is necessary to standardize the protocols for prevention and treatment of this condition in order to make different studies comparable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations